Informationally objectifying beings: A critique on Floridi’s moral status of information objects - Cabangon, Emmanuel Ernest T. (Animo Repository, 2024)
This paper aims to intersect Floridi’s informational theory with the traditional accounts of moral status. Moral status asserts the importance of the entity’s rights and practical respect from other agents. In answering the question “who deserves moral status?”, the classical views of moral status answers this by either referring to Rational, Sentient and Relational beings. However, these competing themes do not recognize existing entities that are not within their conditions, such as historical artifacts and artworks. In contrast, Floridi proposed that all beings are information objects, and being an information object deserve the lowest possible degree of intrinsic value, thus justifying its moral respect. In affirming whether or not an entity is an information object, this is done through a methodology known as Object Oriented Programming (OOP). The methodology includes the interaction of seven functionally specific components that an information object takes into account. Since intrinsic value should be present in order to affirm an entity’s moral status, Floridi suggests that the minimalist degree of intrinsic value is conferred on an information object by another information object in an infosphere. Hence, this paper claims that Floridi’s informational theory of moral status is uniquely different from the arguments proposed by the classical views of moral status, but it has specific limitations. In reconciling these views with Floridi’s framework, the claim is framed by discussing the following: (1) the difference of the nature of beings with information objects, (2) its association with the minimalist degree of intrinsic value, and (3) its limitation.